The Effectiveness of TED-ED Videos on Students’ Speaking Skills in Ninth Grade of Junior High School - Utami, Salsabila Nurjihan; Noerjanah, Siti Luruh Ayu; Ibnus, Nizar (Foreign Language Instruction Probe, 2024)
This research aim to find out students’ speaking skills before and after being taught by using TED-ED videos, to discover students’ speaking skills before and after being taught without using TED-ED videos and to investigate whether there is a significant effectiveness on students speaking skills before and after being taught by using TED-ED videos. Then, this study used quantitative data collection conducted with a quasi-experimental design with a nonequivalent (pretest and posttest) control-group design. The population of this study was ninth-grade students of public Junior High School in Cirebon in the academic year 2022/2023. The sample used purposive sampling techniques with two groups: class IX E was the experimental group, and the control group was IX F. Each class consists of 20 students. The data collections were tests and documentations. The researcher used t-tested by using SPSS. The findings based on the table descriptive analysis showed that there were changed in the pretest scores in the experimental and control classes and the posttest scores in the experimental and control classes. Then, in the table paired sample test showed that that there was a significant effectiveness on students’ speaking skills before and after being taught by using TED-ED videos.